Reliability and validity of the repetitive behavior scale-revised for young Chinese children with autism spectrum disorder in Jiangxi Province - Xiu Luo; Yaoyao Xiong; Mei Gu; Liyun Huang; Zhonghui Lu; Xia Zhong; Shipu Zou (Frontiers Media S.A., 2022)
Restricted and repetitive behaviors (RRBs) are one of the two main diagnostic features of autism spectrum disorder (ASD). To date, a growing body of research on RRB in children with ASD has recently attracted academic attention. The Repetitive Behavior Scale-Revised (RBS-R) was primarily intended for use in evaluating RRBs observed in ASD. This study recruited 381 Chinese children with ASD aged 2-4 years to measure the reliability and validity of the RBS-R. Confirmatory factor analysis (CFA) was applied to the structuring models of the four proposed structural models, indicating that a 6-factor model demonstrated good internal consistency and the best fit based on common overall fit indices. These findings suggest the utility of the Chinese version of RBS-R.